Value-Belief-Norm Theory and Pro-Environmental Behavior: A Study on Blue Collar Workers in Jakarta - Soemantri, Tiara Salsabila; Anzhari, Kautsar; Kosasih, Ovi; Agustini Murwani , Ina (Journal Research of Social Science, Economics, and Management, 2025)
Pollution and climate change have become urgent global challenges, with the Special Capital Region of Jakarta identified as one of the most affected areas. While many citizens have adapted to these environmental pressures, blue-collar workers remain relatively overlooked in studies of ecological awareness and pro-environmental behavior. This research addresses this gap by examining how value orientations influence ecological worldviews and subsequent behavioral outcomes. The objective of the study is to analyze the relationships within the Value-Belief-Norms (VBN) framework, specifically investigating how biospheric, altruistic, and egoistic values influence the New Ecological Worldview (NEP), awareness of consequences, ascription of responsibility, personal norms, consumer willingness, and ultimately environmental citizenship behavior. Using a quantitative approach, data were collected through convenience sampling from 69 blue-collar workers in Jakarta. The analysis employed Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. Results demonstrate that NEP positively influences awareness of consequences, which in turn affects ascription of responsibility, leading to stronger personal norms. Personal norms significantly shape consumer willingness, which further enhances environmental citizenship. The findings highlight the importance of strengthening ecological values and personal responsibility among blue-collar workers as a pathway to foster sustainable behavior and active citizenship in urban environments.